1997
DOI: 10.3109/00365549709011835
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Levofloxacin and Ofloxacin on the Normal Oral and Intestinal Microflora

Abstract: The aim of the study was to study the ecological effects of levofloxacin, compared to that of ofloxacin, on the oral and intestinal human microflora. 10 healthy volunteers received levofloxacin (500 mg) and 10 subjects were given ofloxacin (400 mg) perorally, once daily for 7 days. Saliva and stool samples were obtained prior to drug administration, during administration (days 2, 4 and 7), and after withdrawal of the agents (days 9, 11, 14 and 21). The concentrations of levofloxacin and ofloxacin in the saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…The populations rapidly recovered to the predosing levels after antibiotic dosing ceased. These observations are consistent with those presented in previous reports, in which it was reported that levofloxacin elicited a selective reduction in the gut microbiota and predominantly affected gram-negative aerobic bacteria (18).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The populations rapidly recovered to the predosing levels after antibiotic dosing ceased. These observations are consistent with those presented in previous reports, in which it was reported that levofloxacin elicited a selective reduction in the gut microbiota and predominantly affected gram-negative aerobic bacteria (18).…”
Section: Discussionsupporting
confidence: 93%
“…The levels of fluoroquinolones achieved in the gut model are presented in Table 2. Although there were some variations in the peak fluoroquinolone concentrations between the gut model experiments, the levels achieved were still within the ranges previously reported from in vivo studies (Table 2) (9,18,19). The ciprofloxacin concentrations were below the limits of detection (2 mg/liter) within 10 days of the cessation of dosing.…”
Section: Gut Bacterial Populations (I) Ciprofloxacin Administrationsupporting
confidence: 85%
See 1 more Smart Citation
“…Although some fluoroquinolone antibiotics have enhanced in vitro activity against anaerobes (e.g., moxifloxacin and gatifloxacin) (1,13), studies with human volunteers have demonstrated that none of the currently available agents in this class cause a significant reduction in the density of intestinal anaerobes (2,(6)(7)(8)(9)14). Therefore, we examined the effect of fluoroquinolone antibiotics with various levels of antianaerobe activity on the persistence of VRE stool colonization in mice.…”
mentioning
confidence: 99%
“…50% of marketed drugs are chiral and out of that 50% are available as racemate (an equal mixture of both enantiomers) mixtures [10]. The most important thing here is that these two enantiomers may have same pharmacological action, for example, ofloxacin (R-enantiomer) and levofloxacin (S-enantiomer) which are both antimicrobials of quinolones [11]. One enantiomer may be active and the other may be inactive, the examples are (S)-albuterol, a β2-adrenergic receptor agonist for treatment of asthma, and (S)-omeprazole, a proton pump inhibitor for treatment of gastroesophageal reflux has been shown to be superior to their racemic formulations in clinical trials cause their R-enantiomers are inactive [9].…”
Section: Introductionmentioning
confidence: 99%